Standardization of I-124 by three liquid scintillation-based methods. (December 2019) - Bergeron, D.E.; Cessna, J.T.; Fitzgerald, R.; Pibida, L.; Zimmerman, B.E.
Abstract: A solution of 124 I was standardized for activity by 4πβ(LS)-γ(NaI) live-timed anticoincidence (LTAC) counting, with confirmatory measurements by triple-to-double coincidence ratio (TDCR) and CIEMAT-NIST efficiency tracing (CNET) liquid scintillation counting. The LTAC-based standard was shown to be in agreement (within k  = 1 uncertainties) with previous measurements at NIST and elsewhere. Calibration settings for radionuclide calibrators were determined and a discrepancy with literature values, partially due to a calibration methodology dependent upon an erroneous setting for 18 F, was identified and explained. Highlights: A solution of 124 I was standardized for activity by anticoincidence counting. TDCR and efficiency tracing provided confirmatory measurements. Ionization chamber measurements establish accord with previous efforts. Radionuclide calibrator settings presented and discussed in literature context.